Access to local books: the effects of Read Malawi from a children's rights perspective. (14th August 2019) - Shin, Jaran; Sailors, Misty; McClung, Nicola; Hoffman, James V.; Pearson, P. David; Kaambankadzanja, Davie; Mwale, Liveness
Abstract: Children in low‐income, postcolonial countries such as Malawi have few opportunities with quality reading materials that promote independence as readers. In this study, we argue that access to locally produced text relevant to linguistic and cultural contexts is a fundamental human right for children throughout the world. Situating this study within the intersection of research on children's rights and complementary reading materials, we analyse data from a project in Malawi. We consider the ways in which a respect for children's educational rights – specifically, their rights to access information via children's books – can help them develop their biliteracy. Additionally, we examine how the Read Malawi program contributes to Malawian children's literacy development in both national and official languages. Our findings suggest not only a humanistic need for quality complementary books, but also the empirical justification for books in the hands of children; in particular, an interconnected relationship between borrowing books from school and engagement with Read Malawi was found, especially when we explore children's English proficiency. Through Read Malawi, this study exemplifies what a quality literacy intervention can do in supporting children's Chichewa and English proficiency and improving their rights to quality education.